Does regulation influence microfinance institutions to be more client-responsive? - Zakir Morshed; Moshin Habib; Christine Jubb (International Journal of Financial Studies, 2020)
The regulation of microfinance services is likely to have a wide-ranging influence on the microfinance sector, particularly on institutions and their clients. This paper reveals the impact of a specific regulatory regime, the "Microcredit Regulatory Authority Act, 2006", enacted by the Bangladesh government to monitor and supervise nonprofit nongovernment organizations (NGOs). We analyzed survey and interview data provided by clients of both nonprofit microfinance institutions (MFIs) registered under the Act and nonprofit institutions that are unregistered, all lending only to women. Client-level analysis using fixed effects for specific MFI membership is applied, focusing on the role of regulation by comparing protections as consumers of financial intermediations in terms of financial literacy, awareness, and status of clients of registered and unregistered MFIs. We found compelling evidence of a positive association between the financial status, financial literacy, and financial awareness of clients of registered MFIs, but not unregistered MFIs. These findings support the need for MFIs to implement consumer protection measures and inform their consumers about key issues to achieve improved client outcomes.
Keywords: 330; consumer protection; nongovernment organization; regulation; microfinance; consumer awareness; Bangladesh